Analysis of the Implementation of Good Corporate Governance in Food Companies: PT. Indofood Success Makmur - Kasuma, Achmad Bintang Herida; Rabbani, Rahadian Rashief (MultiTech Publisher, 2024)
PT Indofood Sukses Makmur, a renowned Indonesian food manufacturer, is assessed for Good Corporate Governance (GCG) compliance. The company has grown and transformed over the past two decades, becoming a major food industry participant. Indofood understands the relevance of GCG principles for openness, accountability, and stakeholder value despite its success. This study finds Indofood's GCG principles—transparency, responsibility, accountability, independence, and fairness—strong through literature and company actions. However, financial disclosures and sustainability efforts might be more transparent, accountability systems strengthened, and workplace culture more inclusive and varied. The research recommends that Indofood improve its governance procedures through constant monitoring and improvement to sustain stakeholder confidence and navigate the changing consumer food market.